The Reduced Adaptability of H-Reflex Parameters to Postural Change With Deficiency of Foot Plantar Sensitivity - Sun, Mengzi; Lewis, Kelsey; Choi, Jung Hun; Zhang, Fangtong; Qu, Feng; Li, Li (Frontiers in Physiology, 2022)
The purpose of the project was to examine the influence of Peripheral Neuropathy (PN) severity on the relationship between Hoffmann-reflex (H-reflex) and postures. Methods: Thirty-four participants were recruited. H-reflex (H/M ratio and H-index) during Prone, Standing, the Heel-contact phase of walking was tested, along with foot sole sensitivity. Results: The participants were divided into three groups based on the severity of the foot sole sensitivity deficit: Control, less (LA), and more (MA) affected with both feet 5.07 monofilament test scores ranging from 10, 0-5, and 6-9, respectively. A significant group by posture interaction was observed in the H/M ratio (F3.0, 41.9=2.904, p=.046, ηp2=0.172). In the Control group, the H/M ratio of Prone (22±7%) was greater than that of the Standing (13±3%, p=.013) and Heel-contact phase (10±2%, p=.004). In the MA group, the H/M ratio of Standing (13±3%) was greater than that of the Heel-contact phase (8±2%, p=.011). The H-index was significantly different among groups (F2,28=5.711, p=.008, ηp2=0.290). Post-hoc analysis showed that the H-index of the Control group (80.6±11.3) was greater than that of LA (69.8±12.1, p=.021) and MA groups (62.0±10.6, p=.003). Conclusion: In a Non-PN population, the plantar sensory input plays an important role in maintaining standing postural control. While as for the PN population with foot sole sensitivity deficiency, type Ⅰ afferent fibers reflex loop (H-reflex) contributes more to the standing postural control. The H-index parameter is an excellent method to recognize the people with and without PN but not distinguish the severity of the PN with impaired foot sole sensitivity.